Effectiveness of Forum Play to promote respectful maternity care: A pilot intervention investigating self-reported perception and behaviour among care providers in urban Nepal - Narayani Paudel Ghimire; Pranab Dahal; Sunil Kumar Joshi; Katarina Swahnberg (PLoS ONE, 2026)
Background Ensuring respectful maternity care is crucial to promote positive childbirth experiences among women. Globally, 22–100% women report experiencing at least one form of disrespect and abuse during facility-based birth, with a study in Nepal reporting 100% prevalence. Thus, interventions like Forum Play are needed to promote respectful maternity care but remain scarce. Forum Play is a participatory theatre technique which encourages the participants to create scenes based on their own experiences illustrating a situation of oppression. This study aimed to assess the effectiveness of a pilot Forum Play intervention in promoting respectful maternity care by investigating self-reported perception and behaviour among care providers. Methods A quasi-experimental pre–post study with a control group was conducted among doctors and nurses in two tertiary hospitals in Nepal. Participants involved in providing care or interacting with women during labour and delivery were purposively selected for the intervention and control groups. The intervention group comprised 25 care providers (14 nurses and 11 doctors), while the control group included 75 care providers (42 nurses and 33 doctors). Two half-day Forum Play workshops were conducted separately for nurses and doctors in the intervention hospital. Data were collected using a self-administered structured questionnaire at baseline and two months post-intervention in both groups; however, the design was not strictly parallel. In the control hospital, data were collected later at the same intervals to provide contextual comparison. Data were analysed using IBM statistical package for social sciences version 20. Descriptive statistics (frequency, percentage, mean and standard deviation) were used to measure the self-reported perception and behaviour on disrespect and abuse and perceptions of respectful maternity care. Mann Whitney U test was used to compare groups and Wilcoxon Signed Rank test was used to assess within-group changes before and after the intervention. Results There were no differences in background characteristics between intervention and control groups (p=>0.05), nor in the overall disrespect and abuse of women at baseline (p = 0.09 to 0.35) whereas significant differences were observed at follow-up (p=<0.001 to 0.004, r = 0.33 to 0.61). There were no significant differences in perception scores towards respectful maternity care between the groups at baseline while significant differences were found at follow-up (z = −3.25, p = 0.001 and r = 0.32). The perception score was significantly higher in the intervention group after the intervention (z = −3.073, p = 0.002 and r = 0.61) while no significant difference was observed in the control group (z = −0.120, p = 0.90 and r = 0.05). Conclusion Forum Play as a method of participatory intervention has the potential to enhance positive perception and behavioral change among care providers towards respectful maternity care. Scaling up the Forum Play intervention and systematically exploring women’s experiences are essential to determine its actual effectiveness.